Development and analysis of a pump-driven loop heat pipe unit for cooling a small data center. (September 2017) - Zhou, Feng; Wei, Chuancheng; Ma, Guoyuan
Abstract: Data centers must be cooled appropriately through indoor temperature control in order to improve information technology (IT) equipment reliability. Free cooling is a promising technology for energy conservation in data centers. A miniature pump-driven loop heat pipe (PLHP) unit for free cooling is developed for a small data center. The unit consumes low power and has a high energy efficiency ratio (EER) compared with air conditioners. The operating performance of the PLHP unit installed in the case data center in Beijing was tested and studied. The EERs under different outdoor temperatures were analyzed, and the fitting variation rules were obtained. Compared with air conditioners, the annual energy savings of the PLHP unit for both hours and days were tested and analyzed based on the fitting formula. Results show that indoor temperature is maintained at 18–25 °C, and that the test energy saving ratio is over 20.18%. Hence, the PLHP unit can replace air conditioners for cooling the case data center.